Organisational culture as a part in the development of open innovation - the perspective of small and medium-sized enterprises = Kultura organizacyjna jako czynnik rozwoju open innovation - perspektywa małych i średnich przedsiębiorstw - Szymańska, Katarzyna (Zielona Góra: Faculty of Economics and Management Press)
The ability to introduce various concepts and business models is nowadays a prerequisite of creating a competitive advantage. This is to a large extent closely linked to the ability of enterprises to create, implement and disseminate a variety of innovative solutions. Today the use of open innovation is a necessity. This applies not only to large organisations, but also to small and medium-sized enterprises.
Keywords: kultura organizacyjna; Open innovation; małe i średnie przedsiębiorstwa; organisational culture; small and medium enterprises (SME)